2016
DOI: 10.1021/acs.jafc.6b02390
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Swainsonine and Swainsonine N-Oxide as Trimethylsilyl Derivatives by Liquid Chromatography–Mass Spectrometry and Their Relative Occurrence in Plants Toxic to Livestock

Abstract: There are limited data concerning the occurrence of swainsonine N-oxide in plants known to contain swainsonine and its relative impact on toxicity of the plant material. A liquid chromatography-mass spectrometry method based on a solvent partitioning extraction procedure followed by trimethylsilylation and analysis using reversed phase high-pressure liquid chromatography-mass spectrometry was developed for the analysis of swainsonine and its N-oxide. The concentrations of each were measured in several swainson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Cultures were air-dried and extracted with 2% acetic acid. Swainsonine was analyzed by LC-MS using methods described by Gardner and Cook (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures were air-dried and extracted with 2% acetic acid. Swainsonine was analyzed by LC-MS using methods described by Gardner and Cook (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it has been shown that swainsonine N-oxide is as effective as swainsonine in inhibiting alpha-mannosidase [1]. To better define the swainsonine N-oxide, Gardner et al [52] established an effective method for the detection of swainsonine N-oxide and detected swainsonine N-oxide fro m Alternaria oxytropis. Beyond swainsonine, and swainsonine N-oxide, the other three alkaloids were isolated and identified from the metabolites of Alternaria oxytropis .…”
Section: Discussionmentioning
confidence: 99%
“…"Locoweed," mainly including Astragalus, Oxytropis, and Swainsona species distributed throughout the world, are responsible for the neurologic disease of poisoned livestock and wild life. [1][2][3][4][5] Based on the bioactive principle of the neurologic symptom, the notorious alkaloid swainsonine (SW) (1S, 2R, 8R, 8aR-1, 2, 8-trihydroxyoctahydroindolizine, 1) was isolated by Colegate et al in 1979 from the Swainsona canescens, [6] though Guengerich et al in 1973 first purified this compound from fungus Rhizoctonia leguminicola. [7] In addition, SW was also isolated from the Metarhizium anisopliae as an immunoreactive substance.…”
Section: Introductionmentioning
confidence: 99%